1992
DOI: 10.1212/wnl.42.9.1727
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular effects of human insular cortex stimulation

Abstract: Recent investigations indicate a site of cardiac representation within the left insular cortex of the rat. Moreover, the results of lesion studies suggest left-sided insular dominance for sympathetic cardiovascular effects. It is unclear whether similar representation exists within the human insular cortex. Five epileptic patients underwent intraoperative insular stimulation prior to temporal lobectomy for seizure control. On stimulation of the left insular cortex, bradycardia and depressor responses were more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

65
764
7
33

Year Published

1995
1995
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,146 publications
(869 citation statements)
references
References 20 publications
65
764
7
33
Order By: Relevance
“…The authors concluded that autonomic dysfunction in migraine exhibits laterality with parasympathetic hyperfunction in left-sided migraineurs. This concept of asymmetric cerebral function has been suggested previously in studies on the autonomic control of the heart, where the left hemisphere was found to predominantly affect parasympathetic function while the right hemisphere affects sympathetic function (60)(61)(62)(63). Collectively, these data suggest that ANS plays an important role in migraine pathogenesis, where the SPG in particular may mediate parasympathetic hyperactivity considering the efferent fibers, neurotransmitter, and innervation organs of the ganglion (14)(15)(16)(18)(19)(20).…”
Section: Migraine and The Parasympathetic Nervous Systemsupporting
confidence: 67%
“…The authors concluded that autonomic dysfunction in migraine exhibits laterality with parasympathetic hyperfunction in left-sided migraineurs. This concept of asymmetric cerebral function has been suggested previously in studies on the autonomic control of the heart, where the left hemisphere was found to predominantly affect parasympathetic function while the right hemisphere affects sympathetic function (60)(61)(62)(63). Collectively, these data suggest that ANS plays an important role in migraine pathogenesis, where the SPG in particular may mediate parasympathetic hyperactivity considering the efferent fibers, neurotransmitter, and innervation organs of the ganglion (14)(15)(16)(18)(19)(20).…”
Section: Migraine and The Parasympathetic Nervous Systemsupporting
confidence: 67%
“…It is likely that regions associated with higher processing functions of the brain appear to be specifically and preferentially affected by propofol (Masamoto et al, 2007). Beside, frontal lobe is implicated in the modulation of emotional behavior and in the control of autonomic responses linked to generalized arousal reactions (Oppenheimer et al, 1992). We speculate that the changes of BOLD signals in frontal cortex during propofol anesthesia might be related to a modification of autonomic outflow that contributes to a decrease in arterial blood pressure.…”
Section: Discussionmentioning
confidence: 85%
“…However, interpreting the significance of a structural change within the brain is challenging. The posterior insula has also been implicated in cardiorespiratory regulation (Oppenheimer, Gelb, Girvin, & Hachinski 1992). Lacking insight into to the function of the specific posterior insula cluster identified in this investigation, any conclusions about the functional significance of the increased cortical thickness remain highly speculative.…”
Section: Cortical Thickness Changes In the Posterior Insulamentioning
confidence: 83%